Construction of compound interface in SiCf/mullite ceramic-matrix composites for enhanced mechanical and microwave absorbing performance. Issue 11 (September 2023) - Pan, Haijun; Luo, Fa; Feng, Xin-Yuan; Qing, Yuchang; Chen, Qiang; Wang, Chun-Hai; Ren, Zhaowen; Nan, Hanyi; Wang, Song; Duan, Shichang
Abstract: SiC fiber-reinforced mullite ceramic-matrix (SiCf /mullite) composite is a promising load-bearing and microwave absorption material. However, the strong interfacial bonding strength and low permittivity cause poor mechanical and absorption performance. Herein, we report SiCf /C-SiC/mullite composite containing a carbon nanosphere network (CNSN) in the SiC interface prepared by precursor infiltration and pyrolysis (PIP). Due to the contribution of CNSN towards interface debonding, fiber slipping, and individual fiber pull-out, the composite shows significant improvement in the flexural strength (by 187%, from 56.23 ± 4.89 MPa to 161.69 ± 13.43 MPa) and the failure displacements (by 238%, from 0.080 ± 0.006 mm to 0.271 ± 0.015 mm). Moreover, the real and imaginary parts of complex permittivity ( ε ′, ε ″) are enhanced from 5.57 to 5.98–6.36–7.11 and from 1.27 to 1.95–2.97–4.69, respectively. Under the synergistic effect of appropriate impedance matching in company with effective conductive loss and multiple polarization loss, the effective absorption bandwidth (EAB) increases from 0.98 GHz to the entire X band, and the minimum reflection loss ( RL min ) enhanced from − 14.31 dB to − 41.51 dB.